Spatial distribution of non-financial health protection resources versus the state of health of the population in Poland - Bem, Agnieszka; Ucieklak-Jeż, Paulina (Przestrzenne zróżnicowanie zasobów ochrony zdrowia a stan zdrowia ludności w Polsce, 2016)
The objective of the study is the analysis of the relations between the distribution of non-financial resources of health care protection at a regional level (voivodeships) and the state of health of the female and male population. The study refers, therefore, to a geographical concept, and the potential access to health service benefits. The following research hypotheses were formulated: (H1) non-financial resources are unevenly distributed among the regions; (H2) access to the health care services affects the state of health of females and males; (H3) there are time delays between the observed levels of accessibility and the state of health of the population. Relying on the Perkal method and on the analysis of the correlation between classes of accessibility of services and the state of health of females and males, described by the expected life span at the age of 30, 45 and 60, the truth of the postulated hypotheses was proved
Nauki o Finansach = Financial Sciences, 2016, Nr 4 (29), s. 9-20
Keywords: access to health care services; the Perkal method; regional diversity; dostępność usług zdrowotnych; metoda Perkala; regionalne zróżnicowanie